Alteration of the Rhizosphere Bacteria Community Respond Differently to Plant Growth Promoting Rhizobacteria in Peanut Soil’s Poteran Island - Ekawati, Ida; Wati, Henny Diana; Koentjoro, Maharani Pertiwi; Sudarwati, Herni; Isdiantoni, Isdiantoni; Prasetyo, Endry Nugroho (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2024)
Plant growth-promoting rhizobacteria (PGPR) has been detailed to affect soil microbial exercises or community composition. There is a lack of information on the degree to which PGPR as a biofertilizer concurrently influences the action, estimate, and composition of the soil microbial community. This research investigated the impacts of the timing and frequency of PGPR application as biofertilizers on the rhizosphere bacteria community in arable soil. We compared four treatments in an experimental field site, namely: one-time treatment of PGPR at the beginning of planting (P1), twice treatment of PGPR (P2), 15-days of planting (DP), and 30-DP (P3); and without treatment of PGPR (WP). A total rhizosphere bacteria community fingerprint was surveyed using ribosomal intergenic spacer analysis (RISA) using a culture-dependent and culture-independent approach. The rhizosphere bacteria community was surveyed during 80 DP. The unweighted pair-group method with arithmetic mean (UPGMA) clustering showed that the rhizosphere bacteria community in three-frequency applications of PGPR was more abundant than without PGPR application and one or two PGPR applications. This study revealed that the rhizosphere bacteria community was increased in soil with PGPR application, especially in P3, three dosages of PGPR application. Increasing the rhizosphere bacteria community could strongly influence the clay foam soil nutrient.